(untitled) (Revista de Ciências Agroveterinárias, 2010)
This work had as objective to characterize and evaluate the capacity of copper (Cu) removal of a zeolite available in the high lands of Santa Catarina State, south of Brazil (basalt zeolite), comparing its efficiency with a commercial zeolite coming from Cuba. The zeolite’s mineralogical characterization was performed by X-ray diffractometry. The cationic capacity trade (CTC) was determined by the method of saturation with ammonium. The studies to assess the zeolite’s capacity to remove Cu were carried out in two stages: (i) without changing the ionic force of the solution and the solution pH;(ii) without changing the ionic force of the solution in two values of pH (4.5 and 5.5). The X-ray diffractograms samples in environment and warmed temperatures showed the occurrence of clinoptilolite in the commercial zeolite, and heulandite in the basalt zeolite. The CTC of the commercial zeolite (Clinptilolite) was higher than the basalt zeolite (Heulandite). However, such differences were not reflected in the capacity of copper removal from the water solutions. There were no statistical differences between the two zeolites for the medium percentage of copper removal in pH 8.3. The Cu adsorption percentage was not influenced by the pH increase from 4.5 to 5.5.